The Effectiveness of Motivational Interviewing in Reducing Student Smartphone Addiction - Setiawan, Arif; Sugiharto, Dwi Yuwono Puji; Purwanto, Edy (Universitas Ahmad Dahlan, 2022)
This study examined the effectiveness of motivational interviewing in alleviating students' smartphone addiction. To this end, an experimental study with a repeated pretest-posttest design was applied. This study involved six students recruited using a purposive sampling technique based on their high smartphone addiction level. The data were collected using Kwon et al.'s (2013) smartphone addiction scale -short version (SAS-SV) and analyzed using mixed ANCOVA repeated measure. The motivational interviewing was conducted in four sessions for each participant, which was in the form of an individual counseling session. The study result showed that the mean score of T1 was 56.67 (SD =1.75) and dropped to 30.67 in T4 (SD = 0.82). In general, motivational interviewing is effective in reducing students' smartphone addiction. This study showed that motivational interviewing is recommended for school counselors in order to reduce students' smartphone addiction.